User Engagement Mechanisms of Online Co-Design Service: Does User Innovativeness Matter? - Windasari, Nila A.; Visita, Luksi (Asian Academy of Management Journal, 2019)
The customer’s shifting role makes collaboration between customer and service provider one of the most important aspects in the value co-creation process. The collaboration and active user’s role has prompted co-design to become one of the strategies for successful product development. This research proposes engagement mechanism factors that improve user engagement and encourage customers to use and buy through the co-design web service. The factors are interactive feedback with the service provider and collecting points from social media sharing. We also propose user innovativeness to moderate the predictors and improve user engagement. We utilise a scenario-based experiment for a co-design clothing web store in Indonesia. Results show that additional interactive contact with the service provider will increase a user’s engagement and likelihood of use. The effect is greater for customers with lower levels of innovativeness. In contrast, adding game elements (e.g., points) has no significant contribution to customer engagement and use intention. This research shows the value of engagement mechanisms in enabling the value co-creation process in a co-design platform. This study contributes by providing a framework for the service provider to deploy an engaging co-design service by considering both service provider factors (i.e., engagement mechanics embedded on the web) and customer-related factors (i.e., user innovativeness level) to encourage customers to use and buy through online co-design service.